The Influence of Technology Accepted Model (TAM), Social Influence and Trust on Interest in Using Islamic M-Banking - Navaa, Navaa Tsaltsa Nabila; Ummu, Ummu Salma Al Azizah; Arief, Arief Fitriyanto (Jurnal Ekonomi Syariah Mulawarman (JESM), 2024)
ABSTRACT This study aims to determine the effect of Technology Accepted Model (TAM), Social Influence and Trust on Interest in Using Sharia M-Banking. The variables studied are "TAM, Social Influence and Trust on Interest in Using" as the object of the variable and "use of Sharia M-Banking domiciled in East Jakarta DKJ" as the object of observation. Primary data were collected from the results of collecting respondents' answers through the Google Forms questionnaire and supplemented with previous research and other literature. The results of the study showed that after being calculated using the assistance of Microsoft Excel and SmartPLS 3.0 programs, the technology accepted model (TAM) variable had a significant effect on interest in using Sharia M-Banking, the social influence variable had a significant effect on interest in using Sharia M-Banking, and the trust variable had a significant effect on interest in using Sharia M-Banking.